2013
DOI: 10.1186/1752-153x-7-103
|View full text |Cite
|
Sign up to set email alerts
|

Revealing water’s secrets: deuterium depleted water

Abstract: BackgroundThe anomalous properties of water have been of great interest for generations of scientists. However the impact of small amount of deuterium content which is always present in water has never been explored before. For the first time the fundamental properties of deuterium depleted (light) water at 4°C and 20°C are here presented.ResultsThe obtained results show the important role of the deuterium in the properties of bulk water. At 4°C the lowest value of the kinematic viscosity (1.46 mm2/s) has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
(21 reference statements)
0
22
0
Order By: Relevance
“…Over the last decades the investigation of this object continues to expand introducing corrections to results obtained earlier and supplementing by new data of water properties [2][3][4][5][6][7][8][9][10]. Invariably basic is such physical indicator as freezing temperature of normal and heavy waters.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades the investigation of this object continues to expand introducing corrections to results obtained earlier and supplementing by new data of water properties [2][3][4][5][6][7][8][9][10]. Invariably basic is such physical indicator as freezing temperature of normal and heavy waters.…”
Section: Introductionmentioning
confidence: 99%
“…Results of investigation of physicochemical and biological properties of light water are given in papers [5][6][7][8][9][10][11][12]. Thus, paper [1] provides data on physicochemical properties of light water with D/H = 4, 18 O/ 16 O = 750 ppm; boiling temperature and melting point, kinematics viscosity temperature, density temperature, time of spin-spin relaxation of protons, coefficients of self diffusion, small angle laser light scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, paper [1] provides data on physicochemical properties of light water with D/H = 4, 18 O/ 16 O = 750 ppm; boiling temperature and melting point, kinematics viscosity temperature, density temperature, time of spin-spin relaxation of protons, coefficients of self diffusion, small angle laser light scattering. Paper [12] investigated fundamental properties of light water with D/H = 4.2, 18 O/ 16 O = 910 ppm and 20°C. It is shown that anomalies of density, surface tension, and water viscosity are caused by the presence of deuterium at var ious concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is explained by the fact that the melt water contains a low percentage of deuterium compared with ordinary tap water that is believed to have a positive effect on the tissue cells and metabolism. The melted water in Russia is considered to be a good folk remedy for increasing physical activity of the human body, enhancing the vitality of the organism and has a beneficial effect on metabolism [11].…”
Section: Empirical Evidence On Life Durationmentioning
confidence: 99%